Impact of a standardized order set and medication-use process on medication error rates in sexual assault patients presenting to the emergency department for HIV nonoccupational postexposure prophylaxis. - Segovia, Margaret F; Pallotta, Andrea M; Campbell, Matthew J; Englund, Kristin; Reali-Sorrell, Michele; Shah, Sneha S (American Journal of Health-System Pharmacy, 2023)
Purpose To evaluate the impact of a standardized order set and medication-use process on antiretroviral medication errors in sexual assault (SA) patients presenting to the emergency department (ED) for nonoccupational postexposure prophylaxis (nPEP). Methods In November 2019, a multidisciplinary group collaborated on an initiative to improve the nPEP medication-use process for SA patients presenting to the EDs within a large integrated health system. Electronic medical records of patients 13 years of age or older who presented for SA examination and were prescribed nPEP during the pre- (February 2018-August 2019) and poststandardization (February 2020-August 2021) periods were included. The primary objective was to compare the proportion of patients experiencing a medication error before and after SA/nPEP process standardization. Data regarding the following medication errors were evaluated: incomplete regimen; inappropriate/duplicative regimen; dosing, frequency, or quantity prescribed error; and initiation of nPEP without an HIV test. Results Two hundred six patients met criteria for inclusion. A higher proportion of patients experienced medication errors in the prestandardization group relative to the poststandardization group (46.5% vs 11.9%, P < 0.001). Fifty-five errors were observed in the prestandardization group, compared to 16 errors in the poststandardization group. The majority of errors in the prestandardization group were directly related to antiretroviral regimens, while the majority of errors in the poststandardization group involved initiation of nPEP without an HIV test. Conclusion The standardization of the SA/nPEP process was associated with significantly lower medication error rates. Optimization of medication-use technology is an effective strategy in reducing medication errors.